Business Intelligence Capabilities and AI-Driven Logistics Innovation: The Roles of Decision Support and Supply Chain Visibility - Alzghoul, Amro; Khaddam, Amineh A.; Irtaimeh, Hani J.; Ali, Ahmad (International Review of Management and Marketing, 2026)
This study explores the effects of business intelligence capabilities on AI-driven logistics innovation by conceptualizing two serial mediation mechanisms: decision support and supply chain visibility. Based on the dynamic capability’s perspective and resource-based view, the study has the following argument: BI capabilities will enable logistics firms to gather, integrate, analyze, and convert the data from operations to useful knowledge, which helps in making intelligent decisions. A quantitative, explanatory and cross-sectional research design was used. A structured questionnaire was administered to 327 employees/managers in logistics-related companies to gather data. The data was statistically analyzed by SmartPLS software using structural equation modeling. The results indicated that the business intelligence capabilities have a positive impact on decision support as well as AI-powered logistics innovation. Results show that decision support has a positive influence on supply chain visibility, and that supply chain visibility has a positive influence on AI-enabled logistics innovation. Further results demonstrated that BI capabilities and AI-enabled logistics innovation is serially mediated by decision support and supply chain visibility. The research enlightens the literature by detailing how data-driven functionalities can be turned into AI-powered logistics innovation through enhanced decision-making capabilities and supply chain transparency.